Eye Movements in Fragile X-Associated Tremor/Ataxia Syndrome. Issue 4 (December 2021) - Hall, Deborah A.; Leehey, Maureen A.; Hagerman, Randi J.; Pelak, Victoria S.
Abstract : Background: Fragile X-associated tremor/ataxia syndrome (FXTAS) is a neurodegenerative disorder characterized by ataxia, tremor, and parkinsonism. Eye motility abnormalities on the clinical examination of FXTAS patients have not been formally studied. Methods: A case–control study with fragile X gene mutation carriers with and without FXTAS and normal controls was conducted and included a videotaping of ocular items of the International Cooperative Ataxia Rating Scale (ICARS). A neuro-ophthalmologist blinded to gene status rated nystagmus, ocular pursuit, and saccades. Results: Forty-four cases and controls were recruited, with an average age of 55.2 years (±7.4) and 57% women. Gaze-evoked nystagmus was increased in fragile X gene carriers (odds ratio 1.44, 95% confidence interval: 0.33–7.36) but was not statistically significant. There was no difference in ocular pursuit nor saccade dysmetria between cases and controls. Conclusion: The results show that clinical examination findings of ocular abnormalities, using the ICARS oculomotor disorders movement subscale, are not more common in FXTAS or FMR1 premutation carriers than normal controls on examination in the clinic. Examining a larger cohort of patients with FXTAS would be an ideal next step.